AN OVERVIEW OF THE PERSONAL INCOME TAX AND CAPITAL GAINS TAX REGIME IN NIGERIA - AGBONIKA, JOHN ALEWO MUSA; AGBONIKA, JOSEPHINE ALADI ACHOR (American Journal of Law, 2023)
In Nigeria, the Personal Income Tax is a tax charged on the income of individuals and is imposed on different sources of income like labour, pensions, interest and dividends. Revenues from the Personal Income Tax constitute an important source of income for three tiers of government in Nigeria. Capital gains tax administration in Nigeria is regulated by the Capital Gains Tax Act.[1] The Act is administered by both Federal Inland Revenue Service and the States Internal Revenue Service. Federal Inland Revenue Service deals with the taxation of capital gains arising from the deposal of property by corporate entities while the State Internal Revenue deal with gains on deposal by individual sole traders. The Tax rate is 10% on capital gains. The capital gain is the difference between the sale proceeds from sale of the assets. Expenses that are incidental to the deposal are allowed as a deduction from the sales proceeds. The objective is to provide better understanding of the different ways of assessing and collection of taxes with a view to providing and ensuring improved compliance by the tax payers. The paper further examines the issues relating to persons subject to tax, resident, the key legislation governing imposition of tax in Nigeria including the authorities charged with the responsibility to administer it. In carrying out this research we adopted a theoretical framework by looking at other literature on the subject as basis for our findings and recommendations. Findings revealed that tax has positive significant impact on government revenue in Nigeria. It is therefore recommended that there should be increased tax awareness and campaign in order to enable government generate more revenue from tax to boost its gross domestic products.